Efficiency Problems in the System of Key National Indicators - E. A. Brendeleva (Vestnik MGIMO-Universiteta)
The article talks about the key national indicators characterizing economic development, as well as the problems associated with the aims set in the framework of these indicators. The paper also looks at the possible changes in the existing system to asses the state of national economies and social welfare, as well as in the way institutional characteristics of a particular country are considered in this system, with the final aim of deciding on the states’ long term development strategy.